Assessment of the efficacy and safety of Indulekha Svetakutaja hair oil in management of dandruff: a randomized, double-blind, placebo-controlled study - Shukla, Ravi Kant; Punyani, Supriya; Gudulkar, Susmita; Sachdev, Mukta; Kumari, Ritambhara; Sachdev, Aahan; Shome, Antara (International Journal of Research in Dermatology, 2024)
Background: This study aimed to evaluate the efficacy and safety of Indulekha Svetakutaja Hair Oil in comparison with coconut oil in the management of dandruff through a randomized, double-blind, placebo controlled study. Methods: A total of 110 subjects with clinically diagnosed moderate dandruff were randomly assigned into two groups: Group A (The Indulekha Svetakutaja Hair Oil group, n=55) and Group B (Placebo coconut hair oil group, n=55), where 50 subjects in each group completed the study. The treatment phase was for 4 weeks, followed by a regression phase of 2 weeks. Subjects applied the allotted oil on their scalp, massaged and kept it for a minimum of 30 mins or overnight thrice a week, then washed it with the provided neutral shampoo for a duration of 4 weeks. Dermatological assessments, instrumental measurements and subject self-assessment questionnaire were evaluated in comparison to baseline at weekly intervals throughout the study period. Results: After 4 weeks of treatment, group A demonstrated a significantly greater reduction (p<0.05) in dandruff severity compared to group B. The Total Dandruff scores in Group A showed a significant reduction of 70.62 units while in Group B, it was noted to be 48.79 units. Nearly all participants (98%) in Group A reported a subjective perception improvement in dandruff symptoms compared to Group B. Conclusions: Indulekha Svetakutaja Hair Oil is safe and effective in controlling dandruff and improving scalp and hair health, making it a promising therapeutic option for individuals with dandruff.